PENERAPAN MODEL PEMBELAJARAN BAHASA ARAB BERBASIS SAVI UNTUK MENINGKATKAN MAHAROH KALAM SISWA KELAS X MIPA 2 DI MADRASAH ALIYAH AL-KARIMI GRESIK - Nurhidayati; Hikmah, Khizanatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study focuses on the importance of implementing various teaching methods to prevent students from experiencing boredom in the learning process. Teaching methods play a vital role in delivering educational content effectively and in line with students’ learning styles. Creating an active classroom environment where students are actively engaged is essential to enhance comprehension and retention of the material. In this context, teachers act as facilitators, guiding students towards achieving the skills required for educational goals. This study addresses common issues in Arabic language skills learning, specifically the linguistic and non-linguistic challenges faced by students. It highlights the SAVI (Somatic, Auditory, Visual, Intellectual) learning model as a comprehensive approach that involves all the senses, which has the potential to aid student engagement and retention of knowledge. The methodology of this study involved Classroom Action Research (CAR), utilizing a qualitative descriptive approach. Data were collected through observation, interviews, tests, and questionnaires, analyzing students’ performance and engagement levels before and after implementing the SAVI method. Initial findings revealed that traditional teaching methods resulted in low student engagement and comprehension. However, the transition to a SAVI-based approach showed a marked improvement in student participation and comprehension in Arabic language skills. In the second cycle of the study, substantial improvement in students’ mastery of Maharrah Kalam was observed, indicating the effectiveness of the SAVI model in fostering a more interactive and engaging learning environment. These findings underscore the benefits of incorporating diverse teaching strategies to improve student learning outcomes and highlight the importance of adaptability in teaching methods to meet the diverse needs of students.